Effects of Vane Trailing Edge Deterioration on Flow Phenomena: A CFD Simulation of Broken Scenarios - Benyapa Thammachote; Jitlada Premyothin; Ditthaphat Tanpradit; Atikorn Wongsatanawarid; Daniele Dipasquale; Prasert Prapamonthon (My University, 2023)
Abstract To achieve high thermal and propulsive efficiencies from an aircraft powerplant using an air-breathing system, the turbine inlet temperature (TIT), a critical design-limit variable, must rise. However, the increment of the TIT is limited by the survivability of the turbine material. Beyond the safety zone of the material, the operation can end in failure. For this reason, the turbine nozzle guide vane (NGV) is a critical component of gas turbine engines because it must operate in hot gas environments. Due to the constraints of effective cooling and the thinnest possible shape of the trailing edge (TE), this region can be suddenly or gradually deteriorated by cracks when the turbine is in long-term operation. This situation can have a seriously negative effect on the engine’s performance because the flow field and heat phenomena are different from the usual conditions. Therefore, the problem of vane TE damage is very challenging, and sustainable solutions require a thorough understanding of flow physics and heat transfer mechanisms. A three-dimensional CFD simulation with the SST k-ω turbulence model is used in this work to investigate flow phenomena at the vane trailing edge while subjected to damage effects. The profile of the Mark II vane is used to create vane boundaries in the computational domain. The computational mesh is generated by ICEM and 18 layers are added to the vane surface to capture the flow in the boundary layer. The minimum quality of the mesh is 0.2 and y+ is less than 4.5. The FLUENT software is used as the solver, with second order upwind discretization. Under the compressible flow model, air is used as the burned gas. Broken scenarios in both the streamwise and spanwise directions are presented in a very simplistic manner, with a short, shallow cutback expanding into a long, deep one, namely, 0.1 cm × 1 cm to 0.3 cm × 3 cm. The convergence of the numerical results is considered by the residual of the governing equations. Boundary conditions are set to be the same as experimental data reported by NASA so that numerical results in terms of the pressure distribution along the vane midspan can be validated. The results predicted by the SST k-w turbulence model can provide an acceptable agreement with the experiment. For subsequent simulations, numerical results involving turbulent flow, such as turbulent viscosity, turbulent kinetic energy, vorticity, and streamlines, are compared, and discussed. The findings show that vane TE damage has a significant impact on fluid in motion, particularly the phenomenon of turbulent viscosity. This suggests that heat convection is disrupted.
Keywords: Aerodynamics and Fluid Dynamics Research; Wind and Air Flow Studies